Molecular Genetics and Biology of Head and Neck Squamous Cell Carcinoma: Implications for Diagnosis, Prognosis and Treatment - Ganci, Federica; Sacconi, Andrea; Manciocco, Valentina; Covello, Renato; Spriano, Giuseppe; Fontemaggi, Giulia; Blandino, Giovanni (IntechOpen, 2012)
None